Results of a randomized, double-blind phase II clinical trial of NY-ESO-1 vaccine with ISCOMATRIX adjuvant versus ISCOMATRIX alone in participants with high-risk resected melanoma. Issue 1 (20th April 2020) - Cebon, Jonathan S; Gore, Martin; Thompson, John F; Davis, Ian D; McArthur, Grant A; Walpole, Euan; Smithers, Mark; Cerundolo, Vincenzo; Dunbar, P Rod; MacGregor, Duncan; Fisher, Cyril; Millward, Michael; et al.
Abstract : Background: To compare the clinical efficacy of New York Esophageal squamous cell carcinoma-1 (NY-ESO-1) vaccine with ISCOMATRIX adjuvant versus ISCOMATRIX alone in a randomized, double-blind phase II study in participants with fully resected melanoma at high risk of recurrence. Methods: Participants with resected stage IIc, IIIb, IIIc and IV melanoma expressing NY-ESO-1 were randomized to treatment with three doses of NY-ESO-1/ISCOMATRIX or ISCOMATRIX adjuvant administered intramuscularly at 4-week intervals, followed by a further dose at 6 months. Primary endpoint was the proportion free of relapse at 18 months in the intention-to-treat (ITT) population and two per-protocol populations. Secondary endpoints included relapse-free survival (RFS) and overall survival (OS), safety and NY-ESO-1 immunity. Results: The ITT population comprised 110 participants, with 56 randomized to NY-ESO-1/ISCOMATRIX and 54 to ISCOMATRIX alone. No significant toxicities were observed. There were no differences between the study arms in relapses at 18 months or for median time to relapse; 139 vs 176 days (p=0.296), or relapse rate, 27 (48.2%) vs 26 (48.1%) (HR 0.913; 95% CI 0.402 to 2.231), respectively. RFS and OS were similar between the study arms. Vaccine recipients developed strong positive antibody responses to NY-ESO-1 (p≤0.0001) and NY-ESO-1-specific CD4 + and CD8 + responses. Biopsies following relapse did not demonstrate differences in NY-ESO-1 expression between the study populations although an exploratory study demonstrated reduced (NY-ESO-1) + /Human Leukocyte Antigen (HLA) class I + double-positive cells in biopsies from vaccine recipients performed on relapse in 19 participants. Conclusions: The vaccine was well tolerated, however, despite inducing antigen-specific immunity, it did not affect survival endpoints. Immune escape through the downregulation of NY-ESO-1 and/or HLA class I molecules on tumor may have contributed to relapse.